2021
DOI: 10.1002/dc.24900
|View full text |Cite
|
Sign up to set email alerts
|

The international system for serous fluid cytopathology: Interobserver agreement

Abstract: Background: A number of categorization systems had been developed for the reporting of cytology specimens with the aim of providing uniform definitions, criteria, and diagnostic terminology. The intention of these systems is to improve reproducibility of diagnostic categorization with standardized estimates of malignancy risk. Required for the success of these systems is a high level of interobserver reproducibility for category assignment. Recently, the international system for serous fluid cytopathology (TIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…It is conceivable that use of the Sydney system enhances interobserver agreement by providing a uniform terminology and clear criteria for classification. The rates of agreement observed are in line with those reported using other classification systems 21,25 …”
Section: Discussionsupporting
confidence: 89%
“…It is conceivable that use of the Sydney system enhances interobserver agreement by providing a uniform terminology and clear criteria for classification. The rates of agreement observed are in line with those reported using other classification systems 21,25 …”
Section: Discussionsupporting
confidence: 89%
“…These heterogeneities might stem from a difference in served population-based characteristics, such as the prevalence of cancers, or different diagnostic concepts among institutions and individual pathologists even from the same country. [26][27][28] Furthermore, the follow-up approach to determining the ROM varied among different Jha 2021 15 Pergaris 2021 17 Xu 2021 11 Straccia 2022 12 Ahuja & Malviya 2022 16 Bharti 2022 9 Hou 2021 18b This was excluded from further pooled series because of a lack of data for some categories.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that there was significant heterogeneity in the frequency and ROM in data from different practices, especially for the ND, NFM, and AUS categories. These heterogeneities might stem from a difference in served population‐based characteristics, such as the prevalence of cancers, or different diagnostic concepts among institutions and individual pathologists even from the same country 26–28 . Furthermore, the follow‐up approach to determining the ROM varied among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…adenocarcinoma, lymphoma) are present. As a consequence, interobserver variation should decrease and the risk of malignancy (ROM) should be clarified 17 …”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, interobserver variation should decrease and the risk of malignancy (ROM) should be clarified. 17 In the present review, we have assessed the global impact of the application of TIS, and we have summarised the reported data on the ROM for the five diagnostic categories.…”
mentioning
confidence: 99%